Fabrication of S,N co-doped graphene powders for symmetrical supercapacitors in different aqueous electrolytes - Arvas, Melih Besir; Karatepe, Nilgun; Gencten, Metin; Sahin, Yucel (SPRINGER, 2023)
In this study, coin cell symmetrical supercapacitors were obtained using S,N co-doped graphene powders. S,N co-doped graphene powders were prepared using Yucel's Method with cyclic voltammetry at different potential ranges for selective modification of powders by functional groups. Electrochemical, spectroscopic and microscopic characterization of S,N co-doped graphene powders were carried out. The formation of graphene layers was supported by scanning electron microscopy and Raman analysis. Functional groups formed on the surfaces of S,N co-doped graphene powders were determined by X-ray photoelectron spectroscopy. Specific capacitances of the coin cell symmetrical supercapacitors prepared with S,N co-doped graphene powders were determined by cyclic charge-discharge tests. The highest specific capacitance was 188.3 F.g(-1) and the highest energy and power values were determined as 163.4 Wh.kg(-1) and 2173.9 W.kg(-1), respectively.
Keywords: REDUCED GRAPHENE; ELECTROCHEMICAL PERFORMANCE; ELECTROCATALYTIC ACTIVITY; CARBON NANOSHEETS; FUNCTIONAL-GROUPS; OXYGEN REDUCTION; RATE CAPABILITY; NITROGEN; SULFUR; LAYER; Engineering; Materials Science; Physics